If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2a) + 17 = 0 Reorder the terms: 17 + (2a) = 0 Solving 17 + (2a) = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + (2a) = 0 + -17 Combine like terms: 17 + -17 = 0 0 + (2a) = 0 + -17 (2a) = 0 + -17 Combine like terms: 0 + -17 = -17 (2a) = -17 Divide each side by '2'. a = -8.5 Simplifying a = -8.5
| 3(n+2)-2=4(n-4)-4(n-11) | | 118-(3*b)= | | x(x-8)=-15 | | -3x^2+36x-72=0 | | 25x^2=100 | | 8(2x-1)=72 | | X+46=72 | | 5d-3.3=7.5 | | 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 | | 118-(3xb)= | | 4x-8=x+25 | | 49-2x=7x+16 | | 11-10x=103-38x | | 139-3x=6x+22 | | 2x+3(x-1)=27 | | 3(1+Y)=3-(5y+2) | | -17=-5+4u | | 2-6x=10-8x | | 4j-1+7= | | 15y=14(y+16) | | 3g+3(-5+4g)=1-g | | 2x^2-7x-16=-3x | | 3x+10=45-2x | | 3(6x-4)=22x | | 3(n-1)-2=4(n-4)-(n-11) |